The Books of Sigismund II Augustus in Vilnius University Library: Decorations of Book Covers and New Data about Provenances - Rankelienė, Sondra (Knygotyra, 2020)
In this article, the latest data about the personal book collection items of King of Poland and Grand Duke of Lithuania Sigismund II Augustus in Vilnius University (VU) Library are presented. The authors that have been doing research on these books have not ascertained all of the embossed images that were used for cover decoration and have not identified the locations of where these books were bound and have not disclosed all of the provenances. In order to amend the lack of knowledge about the books of Sigismund II Augustus in VU library, the book covers of the King’s personal library were reviewed de visu and decorative ornaments were described. The ownership signs of the books were registered once again. While describing and comparing these books with the copies in various libraries of the world, the number of physical books (14) and publications in composite volumes (21) kept in VU library was assessed. The name of one book and a publisher’s imprint of two books were specified, eight provenances that were not mentioned by previous authors were registered. While describing book covers, the embossed images were given provisory names. Connections between the supralibros, dates of binding, decorative wheels, single embossed images, and other decorative elements were detected and lead to a reasonable conclusion that eight out of fourteen books from the Sigismund II Augustus collection were bound in Kraków, five were bound by bookbinders in Vilnius, while one was rebound in the 18th century. The identification of tools used by craftsmen that worked in Kraków and Vilnius will allow to ascertain the manufacturing location of similar book covers made in the middle of the 16th century.